PENGARUH MOTIVASI, GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI ASN DI DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN BLITAR - Anang Asfihani; Eka Askafi; Imam Baehaki (Commodities, Journal of Economic and Business, 2021)
This study aims to obtain empirical evidence regarding the influence of motivation, leadership style and work environment on the performance of the employees of the State Department of Industry and Trade, Blitar Regency. The research results are expected to provide input and suggestions that can be used in improving the performance of ASN Disperindag Blitar Regency employees, then to apply the knowledge gained in lectures and as input for further research on human resource problems in the future. This research was conducted on the employees of ASN Disperindag Blitar Regency with 58 respondents. The research method used was a survey method with a quantitative research approach, while the research used the SPSS test technique. The results showed that the Leadership Style and Work Environment significantly influenced the Employee Performance of ASN Disperindag Blitar Regency.